UJI ADAPTASI BEBERAPA VARIETAS PADI GOGO DI ANTARA TANAMAN KELAPA SAWIT MUDA DI KABUPATEN ACEH TIMUR - Idawanni Idawanni; Hasanuddin Hasanuddin; Bakhtiar Bakhtiar (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
The land utilization of young oil palm with several varieties of upland rice become an alternative to increase the farmers income in East Aceh. This study was aimed to obtain new varieties of upland rice that can adapt and give high yields on land of the oil palm trees. The research was conducted on dry land in the area of palm oil plantations in Arul Pinang village, Peunaron sub district, East Aceh from June to December 2014. This study used a randomized block design (RBD) with six treatments and tree replications. The rice plants ware planted on a plot with sized 2 x 9 m. The rice varieties ware consited of Inpago 4, Inpago 5, Inpago 8, Situpatenggang, Batutegi and Arias. The results showed that the varieties affect the growth and yield of rice. varieties Inpago 8 gave the highest yields which produced about 5.78 tonnes ha-1, followed by the varieties of Situ about 5:49 tonnes ha-1, and Batutegi about 4.98 tonnes ha-1.